Interprofessional education: a necessity in Alzheimer’s dementia care—a pilot study - Dressel, Katharina; Ablinger, Irene; Lauer, Anna Andrea; Grimm, Heike Sabine; Hartmann, Tobias; Hermanns, Carina; Schwarz, Marcus; Taddey, Tim; Grimm, Marcus Otto Walter (Frontiers in Medicine, 2023)
Introduction Interprofessional collaboration is seen as an indispensable prerequisite for high-quality health services and patient care, especially for complex diseases such as dementia. Thus, the current project aimed to extend interprofessional and competency-based education in the field of dementia care to the previously understudied therapy professions of nutrition, speech-language pathology, and physiotherapy. Methods A three-day workshop was designed to provide specific learning objectives related to patient-centered dementia care, as well as competences for interprofessional collaboration. Teaching and learning approaches included case-based learning in simulated interprofessional case-conferences and peer-teaching. A total of 42 students (n = 20 nutrition therapy and counseling, n = 8 speech-language pathology, n = 14 physiotherapy), ranging from first to seventh semester, finished the whole workshop and were considered in data analysis. Changes in self-perceived attitudes toward interprofessional collaboration and education were measured by the German version of the UWE-IP. An in-house questionnaire was developed to evaluate knowledge and skills in the field of dementia, dementia management and interprofessional collaboration. Results Participation in the workshop led to significant improvements in the total scores of the UWE-IP-D and the in-house questionnaire, as well as their respective subscales. Moderate to large effect sizes were achieved. All professions improved significantly in both questionnaires with large effect sizes. Significant differences between professions were found in the UWE-IP-D total score between students of speech-language pathology and physiotherapy in the posttest. Students of nutrition therapy and counseling revealed a significant lower level of self-perceived knowledge and skills in the in-house questionnaire pre- and post-testing. Discussion The pilot-study confirms the effectiveness of interprofessional education to promote generic and interprofessional dementia care competencies and to develop positive attitudes toward interprofessional learning and collaboration in the therapy professions, thus increasing professional diversity in interprofessional education research. Differences between professions were confounded by heterogenous semester numbers and participation conditions. To achieve a curricular implementation, interprofessional education should be expanded to include a larger group of participants belonging to different professions, start early in the study program, and be evaluated over the long term.